A security analysis of lightweight consensus algorithm for wearable kidney. (7th October 2022) - Jain, Saurabh; Kumar, Adarsh
In recent times, blockchain has encouraged innovations to handle challenges in many practical applications in which traditional approaches are not found to be successful. This work has proposed a game theory-based approach for consensus building in a distributed network. In this work, the wearable kidney model is analysed to understand the working of the game-theory-based consensus model. The lightweight consensus algorithm consumes fewer resources (suitable for resource constraint devices) and provides an efficient solution to simulate the functionality of a wearable kidney model. The comparative analysis of the result shows that the proposed approach is efficient in fast bit-matching and quick consensus establishment and the kidney blood and urine production are mapped to almost ideal conditions, and variations in delay for bit-matching and algorithm executions are evaluated after that. The comparative analysis shows that algorithm 1 outperforms (at least 2.1%) algorithm 2 in delay analysis because of less distributed functionality.